2019
DOI: 10.3390/w11091855
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Trends and Seasonality Detection of the Observed Flow in Yangtze River Using Mann-Kendall and Sen’s Innovative Trend Method

Abstract: Trend analysis of streamflow provides practical information for better management of water resources on the eve of climate change. Thus, the objective of this study is to evaluate the presence of possible trends in the annual, seasonal, maximum, and minimum flow of Yangtze River at Cuntan and Zhutuo stations in China for the period 1980 to 2015. The assessment was carried out using the Mann–Kendall trend test, and the innovative trend analysis, while Sen’s slope is used to estimate the magnitude of the changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
117
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(120 citation statements)
references
References 68 publications
3
117
0
Order By: Relevance
“…As a non-parametric statistical test, it is also not affected by outliers. The M-K test is often used to quantify the significance of hydrometeorological time series trends [11,[44][45][46][47]. The M-K test is given below:…”
Section: Mann-kendall Testmentioning
confidence: 99%
“…As a non-parametric statistical test, it is also not affected by outliers. The M-K test is often used to quantify the significance of hydrometeorological time series trends [11,[44][45][46][47]. The M-K test is given below:…”
Section: Mann-kendall Testmentioning
confidence: 99%
“…The magnitude of these changes are of the order of a few tenths of a dB and likely result from maintenance actions (such as fiber re-splicing) on the fiber plant. As the data do not follow a normal distribution, non-parametric statistical test methods have been used in the following steps [9,10].…”
Section: Trends In Optical Span Loss Detected Usingmentioning
confidence: 99%
“…They reported that the construction of TGD had reduced the flow in the downstream side of the river, which has negatively impacted the ecosystem. However, at the same time, it helps to reduce peak flows [33]. They also reported that IHA provides considerable useful information on the ecosystem after the hydrologic alteration.…”
Section: Introductionmentioning
confidence: 99%